Reproductive Biology of Carp (Cyprinus carpio) in Batu Bulan Reservoir, Sumbawa, West Nusa Tenggara - Khoirul Fatah Muis (Journal of Global Sustainable Agriculture, 2021)
Research about carp (Cyprinus carpio) reproductive biology in Batu Bulan Reservoir was conducted in April, May, July, and October 2016. This study aims to determine some biological aspects include the degree of gonad maturity, fecundity, spawning frequency and season, and length of the first gonad maturity. The results showed the sex ratio between male and female fish in April (1:5), May (1:3), July (1:3), and October (1:3), with an average of 1:3.5 with the Chi-Square test on the confidence interval. 95%, it turns out that the sex ratio does not follow the 1:1 pattern, or the sex ratio of the fish is not balanced. TKG II carp occurred every month of observation, while the ripe fish of TKG IV gonads were founded only in April, July, and October. The highest percentage of female fish ripe for TKG IV gonads was 45.32%, and males 67.40% were found in October. The size of the ripening female carp size in Batu Bulan Reservoir is 20.16 cm. Carp fecundity ranges from 1,439 to 40,281.